Bioethicists Can and Should Contribute to Addressing Racism. Issue 4 (2nd April 2016) - Danis, Marion; Wilson, Yolonda; White, Amina
Abstract : The problems of racism and racially motivated violence in predominantly African American communities in the United States are complex, multifactorial, and historically rooted. While these problems are also deeply morally troubling, bioethicists have not contributed substantially to addressing them. Concern for justice has been one of the core commitments of bioethics. For this and other reasons, bioethicists should contribute to addressing these problems. We consider how bioethicists can offer meaningful contributions to the public discourse, research, teaching, training, policy development, and academic scholarship in response to the alarming and persistent patterns of racism and implicit biases associated with it. To make any useful contribution, bioethicists will require preparation and should expect to play a significant role through collaborative action with others.